TEN EFFECTIVE TIPS WHICH BRING TO EFFECTIVE ASSESSMENT IN TEACHING ADULTS - Muradkasimova, K.S. (SCIENCE and SOCIETY, 2017)
The given article considers some problems that can occur in teaching adult learners. Moreover, it is focuses on importance of understanding the needs of adults. The author of the article it suggests several effective ways of motivating and assessing adult learners to achieve active learning.